Informational theory of consciousness - Železnikar, Anton P. (Informatica (Ljubljana), 1997)
What is consciousness from a philosopher's, cognitivist's, physicist's, and informatician's point of view? Physicists attempt to tackle the problem by theoretical means of quantum theory 20, 10, 16, 30, 17, 14, philosophers by a debate on qualia 4, 23, cognitivists claim description and explanation 2,21, for example. Informaticians develop a theory of the informational based on the new ground of informational arising 33, 34, 36, 37, 40, 42, 43, 44, 45. This theory togeher with its formalism seems to meet the requirementsfor consciousness description, development, emerging, vanishing, modeling, and non-computability, although the principles of informational arising must be thought and elaborated to the new possible and necessary details. The paper presents two basic metaphisicalistically organized conceptsof consciousness: the general (Fig. 2) and the standard one (Fig. 3). On this ground, an initial informational shell of the generalized and standardized metaphysicalism of consciousness system z transliteracija gotice in Fig. 7 is presented. The shell can be filled with concrete consciousness components (e.g., intention, experience, memory, understanding, etc.), functioning as operand markers in the scheme; they can be further and additionally (in parallel) decomposed in the form of their own and arbitrarilycomplex informational systems.
Keywords: metafizika; teorija informacij; zavest